Teresa Cabré, «Terminology. Cognition, language and communication», Amsterdam/Filadèlfia, John Benjamins, 2023, IVITRA Research in Linguistics and Literature Studies, Editions and Translations, 36, 371 p. - Cuenca Ordinyana, Maria Josep (Caplletra. Revista Internacional de Filologia, 2024)
Ressenya sobre el llibre de Teresa Cabré, Terminology. Cognition, language and communication, Amsterdam/Filadèlfia, John Benjamins, 2023, IVITRA Research in Linguistics and Literature Studies, Editions and Translations, 36, 371 p., ISBN: 978 90 272 1402 7.